If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5-4m=23
We simplify the equation to the form, which is simple to understand
-5-4m=23
We move all terms containing m to the left and all other terms to the right.
-4m=+23+5
We simplify left and right side of the equation.
-4m=+28
We divide both sides of the equation by -4 to get m.
m=-7
| 3(-3)-[(-3)(-3)]=f | | 81=-3(5k-2) | | 4x-7(x+9)= | | (5v)(4)(6k)= | | 8x=36x+21 | | 6x-8(-8x-6)=-22 | | 8x=36x+18 | | 6(7-f)+f=36+j | | 1p-5+5p=-4-6+8p-5 | | .75t-1.25=.3t | | 4(-2b+8)=96 | | 2x+6(3)=x(4)+(8) | | -4=w+14 | | -3p=5 | | 2x+4x-7+2=31 | | 2+b=144 | | 20+.15x=37.25 | | (12x-6)16= | | 4(-7+1)+7(w-8)+13= | | (x+4)=64 | | 16r^2+32r-105=0 | | .2-.01(x+2)=-.03(2-x) | | 2x+b=144 | | -9(x)=6 | | 8y^2+28-60=0 | | 4(7)-4x=20 | | 8n=-2 | | 2(5x+5)= | | -3x^2=180 | | 10x^2+11x+8=0 | | 3x+1-2x=-3 | | 2(4x+3)=-4+3x |